2023
DOI: 10.1021/acs.accounts.2c00701
|View full text |Cite
|
Sign up to set email alerts
|

Urea- and Thiourea-Based Receptors for Anion Binding

Abstract: Conspectus Over the past five decades, significant progress has been made in the field of anion recognition with a diverse variety of synthetic receptors because of the fundamental importance of anions in chemical, environmental, and biological processes. In particular, urea- and thiourea-based molecules offering directional binding sites are attractive receptors for anions due to their ability to bind anions employing primarily hydrogen-bonding interactions under neutral conditions and have gained a recent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Noteworthily, literature examples of sulfate-selective receptors frequently invoke a hydrophobic effect from host encapsulation of sulfate anions, which shields the highly hydrophilic anion and assists its desolvation in aqueous environment. 54,[69][70][71][72][73][74][75] In contrast, sulfate anion induces a large-amplitude co-conformational change in the interlocked backbone of C, bringing the urea donors in the two macrocycles in proximity for convergent sulfate binding. The high flexibility and ability to undergo large-amplitude co-conformational change thus enable the catenane host to adapt to ionic guests of different size, charge, geometry and binding stoichiometry (i.e., 1:1 binding of monocationic, spherical Cu + and 1:2 binding of dianionic, tetrahedral SO4 2-).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthily, literature examples of sulfate-selective receptors frequently invoke a hydrophobic effect from host encapsulation of sulfate anions, which shields the highly hydrophilic anion and assists its desolvation in aqueous environment. 54,[69][70][71][72][73][74][75] In contrast, sulfate anion induces a large-amplitude co-conformational change in the interlocked backbone of C, bringing the urea donors in the two macrocycles in proximity for convergent sulfate binding. The high flexibility and ability to undergo large-amplitude co-conformational change thus enable the catenane host to adapt to ionic guests of different size, charge, geometry and binding stoichiometry (i.e., 1:1 binding of monocationic, spherical Cu + and 1:2 binding of dianionic, tetrahedral SO4 2-).…”
Section: Resultsmentioning
confidence: 99%
“…Advancing this eld, hostmediated liquid-liquid extraction (LLE) has emerged as a powerful approach to impart enhanced selectivity and high binding affinities for desired guest ions. [9][10][11][12] Research into hostmediated LLE has explored the inuence of receptors on cation, 13 anion, 14 and ion-pair 15 extraction. A signicant body of this work has focused on the development of cation receptors, whereas complementary studies on anion receptors have lagged in comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The urea/thiourea moiety forms hydrogen bonds with certain anions, typically oxoanions like H 2 PO 4 − or carboxylates, but also with halide anions (see the complexation of fluoride anion in Scheme 1). 22 Many studies have focused on increasing the binding constant ( cf. Scheme 1, eqn (1)), on increasing selectivity for certain anions, and on improving the sensitivity by coupling urea/thiourea with efficient chromophores and fluorophores, which are active in UV-vis spectrophotometry/colorimetric analysis or spectrofluorimetry (see the excellent reviews by Kundu et al , 22 Li et al 23 or Bregović et al 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…22 Many studies have focused on increasing the binding constant ( cf. Scheme 1, eqn (1)), on increasing selectivity for certain anions, and on improving the sensitivity by coupling urea/thiourea with efficient chromophores and fluorophores, which are active in UV-vis spectrophotometry/colorimetric analysis or spectrofluorimetry (see the excellent reviews by Kundu et al , 22 Li et al 23 or Bregović et al 24 ). An important observation was made by Boiocchi et al in 2004, who studied interactions of N , N ′-bis(4-nitrophenyl)urea with a series of various anions (including strongly interacting carboxylates, H 2 PO 4 − , F − and others) in acetonitrile and DMSO and showed that the interaction of the sensor with the fluoride anion was different.…”
Section: Introductionmentioning
confidence: 99%